Translation Validity and Reliability of Modified Social Expressive Language and Language Comprehensive Subscales of the Child Development Inventory for Children with Autistic Disorder (Thai Version) - Suttipong, Punyanoot; Suttharangsee, Wandee; Nukaew, Orawan (Journal of Research in Nursing-Midwifery and Health Sciences, 2019)
The purpose of this study was to translate and examine the validity and reliability of the modified Thai version of social, expressive language and language comprehensive subscales of the Child Development Inventory (CDI). Forward and backward translation was applied. The process followed the back-translation procedure of WHO guideline. To test the validity and reliability of the CDI, content validation process was verified by five experts and reliability process was tested by thirty participants. The results showed that the modified CDI included similar content as the original. The content validity was high (Content Validity Index: CVI = .85 – 1.00) while the internal consistency reliability for the overall questionnaire was also high (Kuder-Richardson 20: KR-20 = .88 - .94). In conclusion, the translation this modified subscale of CDI into Thai was successfully conducted. The Thai version of this subscale can be used in the assessment of the social, expressive language, and language comprehensive skills among Thai children with autistic disorder.